2015
DOI: 10.1002/ccd.26053
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent cerebral ischemia after patent foramen ovale percutaneous closure in older patients: A two‐center registry study

Abstract: Recurrent cerebral ischemia after PFO closure is more frequent in older patients and could most likely be associated to conditions related to age (atherosclerosis, atrial fibrillation), than to paradoxical embolism. The procedure is as safe as in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
(20 reference statements)
2
20
0
Order By: Relevance
“…These findings should thus be interpreted carefully because patients were relatively younger and the follow-up period was short. Other studies with older patients showed less benefit of percutaneous PFO closure compared to younger patients [4, 5]. However, these studies evaluated all causes of stroke recurrence, not only PFO-related cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings should thus be interpreted carefully because patients were relatively younger and the follow-up period was short. Other studies with older patients showed less benefit of percutaneous PFO closure compared to younger patients [4, 5]. However, these studies evaluated all causes of stroke recurrence, not only PFO-related cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies did not include elderly patients (age ≥ 60 years), and little is known about the clinical benefit of percutaneous PFO closure in older patients. In addition, previous studies have shown that recurrent cerebral ischemia after PFO closure was higher in older than in younger patients [4, 5]. However, PFO-related recurrent cerebral ischemia was not sufficiently evaluated in these studies.…”
Section: Introductionmentioning
confidence: 96%
“…Most of studies about PFO closure included young patients (<55 years old). A recent study, compared the outcomes of PFO closure between a young (<55 years old) and an old group (>55 years old) of patients 20 . It was found that in older patients, PFO closure was as safe as in younger patients, but recurrent cerebral ischemia was more frequent and likely this is associated to conditions related to age than to paradoxical embolism 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The panel found 8 studies (2 RCT, 6 observational) that reported on antithrombotic regimens including duration and outcomes (Table 3). Four other studies (3 observational [52][53][54] and 1 RCT 12 ) reported a regimen of 3 months of dual antiplatelet therapy (DAPT) followed by aspirin monotherapy. These studies reported associated stroke rates of 0, 4.3, 1, and 0 per 1000 patient-years, respectively.…”
Section: Recommendationmentioning
confidence: 99%